Kewenangan Pengadilan Negeri dalam Penyelesaian Sengketa Tanah: Telaah dari Perspektif Hukum Islam - Nur Anshari; Auliaurrahman Auliaurrahman (Al-Widad, 2025)
This paper discusses the authority of the District Court in resolving land disputes in Indonesia, with reference to the perspective of Islamic law. The aim of this research is to explore the role of the District Court in handling land disputes and to compare the implementation of Indonesia's positive law procedures with the principles of Islamic law. In the context of Indonesia's positive law, land disputes are resolved through the district court, emphasizing formal and administrative procedures based on the Basic Agrarian Law (UUPA) and related regulations. In contrast, Islamic law prioritizes principles of consultation, mediation, and social justice before involving the Sharia Court if necessary. This discussion also identifies differences in proving land ownership, where positive law in Indonesia relies more on administrative documents, while Islamic law emphasizes testimony and evidence that is valid according to Sharia. The results of the study show that despite significant differences in the approach of both legal systems, both share the same goal of ensuring justice in resolving land disputes. This study recommends the need for a deeper understanding of the integration of Islamic law in resolving land disputes in pluralistic Indonesia.